The pottery (Scottish Historical and Archaeological Internet Reports, 2003)
An assemblage of 6633 sherds derived from the excavations at Kelso and were mostly post-medieval with the exception of an important medieval group from Wester Kelso/Floors Castle, Trench 3. This included White Gritty Ware in a sealed context and associated with continental imports which have provided important dating evidence. A smaller assemblage of 2292 sherds was found in Peebles, and, again White Gritty Ware was the most common type. This was also the case for the small assemblage of 411 sherds from Cuddyside. The material fills an important gap in the study of medieval Scottish ceramics and specialists are now in a position to attempt an overview of Scotland's earliest native industry. The outstanding problem is the lack of kiln sites.